METHODS OF COMPLEX REHABILITATION OF PATIENTS WITH OSTEOARTHRITIS (REVIEW OF LITERATURE) (World Bulletin of Public Health, 2022)
The article provides a review of the literature on the methods of complex treatment of osteoarthritis. Medicinal and rehabilitation measures for osteoarthritis are considered. According to the literature, despite the complex treatment of arthrosis with nonsteroidal anti-inflammatory drugs and chondroprotectors, it is not effective enough. Therefore, depending on the pathogenetic link of arthrosis, it is necessary to study complex restorative methods of treating this disease